(untitled) (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2022)
Background: Recent legislation regarding medical assistance in dying (MAiD) has important implications for nursing practice and education. It follows that Canadian nursing programmes must integrate theoretical and clinical practice related to MAiD in current curricula. Understanding student knowledge and comfort regarding MAiD provides important direction for developing curricula. Purpose: To explore the understanding and comfort levels of BSN students regarding MAiD. Methods: An applied health research methodology drawing on Interpretive Description was employed. Forty BSN students were surveyed before receiving MAiD education delivered through coursework and clinical experiences; 32 students participated in post intervention surveys; six students participated in individual interviews. Results: Three major themes emerged from data analysis: prior experience and lack of experience; personal beliefs and role challenges; need for knowledge. Student understandings and comfort level levels related to MAiD were strongly influenced by their previous experiences, personal values and beliefs, and knowledge of MAiD policies and practices. Both theory courses and clinical experiences related to MAiD had positive impacts on students’ knowledge and comfort levels. Conclusions: Study findings draw attention to the need for improved education related to end of life and MAiD through both theory courses and clinical practicum experiences to improve student knowledge and comfort levels.